2017
DOI: 10.5147/pggb.v1i1.146
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Root and Shoot Traits in the ‘Essex’ By ‘Forrest’ Recombinant Inbred Line (RIL) Population of Soybean [Glycine max (L.) Merr.]

Abstract: Crop productivity is severely reduced by water deficit and drought in many plant species including soybean. Improved root and shoot traits can contribute to drought tolerance ability of the plant. This research was conducted to identify QTL that underlie several root and shoot traits in the ‘Essex’ by ‘Forrest’ (ExF RILs, n=94) recombinant inbred line (RIL) soybean population. Field collected samples were used for gathering phenotypic data of basal root thickness (BRT), lateral root number (LRN), maximum root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 40 publications
(8 reference statements)
3
35
0
Order By: Relevance
“…It has been reported that RA traits could be dramatically influenced by growth stage and environmental factors, such as aerenchyma formation was a result of flooding ( Chimungu et al, 2015 ), which may affect soil exploration by plant roots ( Shimamura et al, 2010 ) and further indirectly influence QTL identification for RA and BNF traits. For example, nine RA QTLs in soybean have been identified under field conditions ( Brensha et al, 2012 ), but with plants that had been grown in pots for 3 weeks before being transferred into field plots. None of these QTLs is consistent with any QTL identified here.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that RA traits could be dramatically influenced by growth stage and environmental factors, such as aerenchyma formation was a result of flooding ( Chimungu et al, 2015 ), which may affect soil exploration by plant roots ( Shimamura et al, 2010 ) and further indirectly influence QTL identification for RA and BNF traits. For example, nine RA QTLs in soybean have been identified under field conditions ( Brensha et al, 2012 ), but with plants that had been grown in pots for 3 weeks before being transferred into field plots. None of these QTLs is consistent with any QTL identified here.…”
Section: Discussionmentioning
confidence: 99%
“…In most crop plants, genetic variations exist for RSA, which enables successful mapping of quantitative trait loci (QTLs) and identification of genes associated with root traits (Prince et al ). Most root studies in soybean have utilized bi‐parental mapping populations to map QTLs for root traits in the seedling stage in controlled greenhouse conditions (Liang et al ; Zhou et al ; Brensha et al ; Liang et al ; Manavalan et al ; Prince et al ) with the exception of a study aimed at mapping QTLs for fibrous root score for plants grown in the field (Abdel‐Haleem et al ). Studying root traits of mature plants is important due to varied responses to soil and climatic conditions when compared to the seedling stage in controlled conditions (Watt et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional soybean mapping studies have identified numerous root quantitative trait loci (QTL; Abdel-Haleem, Lee, & Boerma, 2011;Brensha et al, 2012;Kassem et al, 2006;Manavalan et al, 2015;Prince, Song, et al, 2015;Rong et al, 2011), but few have identified underlying genes within the detected QTLs (Brensha et al, 2012;Manavalan et al, 2015;Prince, Song, et al, 2015). However, the identification of genes involved in specific biological processes and the subsequent categorization of functional effects on RSA are lacking in soybean.…”
mentioning
confidence: 99%
“…The number and thickness of lateral roots were associated with soybean performance in water-deficit soils that represent different target growing environments (Prince, Murphy, et al, 2015). So far, no genes responsible for lateral root number (LRN) have been cloned in soybean, although some QTLs have been mapped (Brensha et al, 2017;Manavalan et al, 2015;Prince, Song, et al, 2015). The formation of a lateral root is a major determinant of a plant's RSA (Pérez-Torres et al, 2008) and this is regulated by auxin signalling (Satbhai, Ristova, & Busch, 2015), surrounding cell wall properties (Péret et al, 2009;Roycewicz & Malamy, 2014).…”
mentioning
confidence: 99%